2022
DOI: 10.1002/biot.202100655
|View full text |Cite
|
Sign up to set email alerts
|

Model‐driven design of synthetic N‐terminal coding sequences for regulating gene expression in yeast and bacteria

Abstract: N‐terminal coding sequences (NCSs) are key regulatory elements for fine‐tuning gene expression during translation initiation—the rate‐limiting step of translation. However, owing to the complex combinatory effects of NCS biophysical factors and endogenous regulation, designing NCSs remains challenging. In this study, a multi‐view learning strategy for model‐driven generation of synthetic NCSs for Saccharomyces cerevisiae and Bacillus subtilis are implemented, which are widely used in laboratories and industrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…By inspecting MGEM mutants, we discovered that in terms of sequence position, the N-terminus was the most important, with the majority of amino acids remaining unchanged in this region (Figure 2E,F). This suggested that the N-terminus is generally evolutionarily optimized for expression efficiency, which also supports why it is widely used for protein expression optimization [86][87][88] . A short hotspot at the very last position in the C-terminus was frequently mutated, which is known as a signal involved in protein degradation 5,6 .…”
Section: Discussionmentioning
confidence: 66%
“…By inspecting MGEM mutants, we discovered that in terms of sequence position, the N-terminus was the most important, with the majority of amino acids remaining unchanged in this region (Figure 2E,F). This suggested that the N-terminus is generally evolutionarily optimized for expression efficiency, which also supports why it is widely used for protein expression optimization [86][87][88] . A short hotspot at the very last position in the C-terminus was frequently mutated, which is known as a signal involved in protein degradation 5,6 .…”
Section: Discussionmentioning
confidence: 66%
“…The N-terminal coding sequence (NCS) is a rate-limiting step in translation and an important element in gene regulation. Wang et al [ 137 ] applied a multiview learning strategy for NCS synthesis in S. cerevisiae . Two models were developed through model training and used to upregulate and downregulate gene expression.…”
Section: Systems Metabolic Engineeringmentioning
confidence: 99%
“…52−54 In summary, as a crucial component for functional expression, the application of direct evolution for modifying proteins is a prospective technological advancement in the field of molecular biology, which holds immense potential for advancing the rapid development of monoterpenoids biosynthesis. 55 3.3. Downregulating the Competitive Pathway Flux.…”
Section: Protein Engineeringmentioning
confidence: 99%
“…One example is that Jiang et al deduced the microscopic mechanism underlying the high activity of geraniol synthase from Catharanthus roseus ( CrGES ) through structural prediction. Subsequently, they fused ERG20 F96W–N127W with tCrGES (the randomly truncated geraniol synthase) to obtain the optimal pairing, eventually achieving 1.68 g/L geraniol titer in S. cerevisiae . In summary, as a crucial component for functional expression, the application of direct evolution for modifying proteins is a prospective technological advancement in the field of molecular biology, which holds immense potential for advancing the rapid development of monoterpenoids biosynthesis …”
Section: Multiple Strategies For the Production Of Monoterpenoidsmentioning
confidence: 99%